2021
DOI: 10.1037/spq0000428
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of equity: Discipline disproportionality and SWPBIS implementation in urban schools.

Abstract: School-wide positive behavioral interventions and supports (SWPBIS) frameworks have been suggested as a promising approach to reducing disproportionality in school discipline practices; however, few studies have tested this potential, and findings have been mixed. In our sample of 27 urban schools and approximately 15,000 students, risk difference and ratio trajectories for office discipline referrals (ODRs) across 3 years of Tier I implementation evidenced sustained or, in some cases, heightened disproportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 24 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Globally, within educational environments it is crucial to recognize systemic inequities that can be perpetuated (45,46), and how those inequities can give rise to societal disparities related to race, gender, ethnicity, social class, and other factors (47). To address these concerns, there has been an increasing emphasis on restorative practices being used in schools to provide "safer and more positive school communities, offer alternatives to exclusionary practice, and promote equity" (48). Schools and school districts bear the responsibility of addressing educational equity.…”
Section: Restorationmentioning
confidence: 99%
“…Globally, within educational environments it is crucial to recognize systemic inequities that can be perpetuated (45,46), and how those inequities can give rise to societal disparities related to race, gender, ethnicity, social class, and other factors (47). To address these concerns, there has been an increasing emphasis on restorative practices being used in schools to provide "safer and more positive school communities, offer alternatives to exclusionary practice, and promote equity" (48). Schools and school districts bear the responsibility of addressing educational equity.…”
Section: Restorationmentioning
confidence: 99%
“…Some broader school-wide interventions are theorized to reduce inequities, but in a recent systematic review, Cruz and colleagues (2021) identified mixed effects of randomized controlled trials of school-wide PBIS and restorative justice on discipline disparities. Although there is evidence both approaches reduce overall rates of ODRs or suspensions (Bradshaw et al, 2010;Gregory et al, 2018), including for marginalized groups, neither approach demonstrated a significant reduction in the racial gap (Barclay et al, 2022;McIntosh, Gion, et al, 2018;Zakszeski et al, 2021). Some classroom-level studies have shown the promise of one-to-one teacher coaching to reduce disparities (Bradshaw et al, 2018;Gion et al, 2021;Gregory et al, 2016), but this approach requires intensive support for individual teachers at substantive cost to implement at scale and with the requirement that individual teachers elect to receive coaching for equity, a substantial barrier to intervention.…”
Section: Interventions To Reduce Disparitiesmentioning
confidence: 99%
“…We are delighted to announce the article(s) of the year. For 2021 (acknowledged during the 2022 APA convention), we had one winner (i.e., McIntosh et al, 2021) and two honorable mentions (i.e., Sullivan et al, 2021; Zakszeski et al, 2021). Zakszeski et al found that school-wide positive behavioral intervention and supports (SWPBIS) either did not impact or in some cases heightened discipline disproportionality for students identifying as Black/African American or Latinx/Hispanic.…”
Section: Journal Impactmentioning
confidence: 99%